High propensity to pay dividends by state-controlled companies in Poland: Tunneling or maturity effect? - Mieczysław Kowerski (e-Finanse: Financial Internet Quarterly, 2015)
Usage of a random effects panel logit model have shown in this paper that the high propensity to pay dividends by the state-controlled companies quoted on the Warsaw Stock Exchange over the last years was not a result of the tunneling effect but was the maturity effect. The state-controlled companies which pay dividends fulfil the maturity effect criteria as they are big, profitable, have low investment opportunities and financial leverage, and are characterised by low risk associated with investing in their shares. The additional evidence of a reasonable and stable dividend policy pursued by the state-controlled companies are: payout ratio on the level of slightly more than 50% and lower by almost 8 percentage points than in the other companies; and relatively rare use of the reserve capital for dividends. However, state-controlled companies listed on the WSE are mostly commercial and of a fi scal nature for the state, which may create a temptation for tunneling.
Keywords: E44; G17; G35; 330; Warsaw Stock Exchange; state-controlled companies; dividend policy; maturity effect; tunneling effect